Young adult cancer survivors' experiences with a mindful self-compassion (MSC) video-chat intervention: A qualitative analysis. Issue 6 (2nd November 2018) - Lathren, Christine; Bluth, Karen; Campo, Rebecca; Tan, Winfield; Futch, Will
ABSTRACT: Young adult cancer survivors (YACS) are a vulnerable population that reports high anxiety, social isolation, and feelings of inadequacy after cancer treatment completion. Mindful self-compassion (MSC) provides strategies for coping with suffering. We explored how MSC practices addressed the psychosocial needs of a nationally recruited YACS sample ( N  = 20, all female, age M  = 27.00, various cancer types) that participated in an 8-week MSC video-chat intervention. Descriptive qualitative analysis of the intervention recordings revealed three YACS' psychosocial needs: peer isolation, body concerns, and health-related anxiety. MSC practices addressed these in a number of ways including: self-reliance for emotional support, common humanity within the YACS community, gratitude, self-kindness, and acceptance. Meanwhile, the body scan practice initially triggered distress for some; implications are discussed.